Identification and Characterization of Anaplasma phagocytophilum Proteins Involved in Infection of the Tick Vector, Ixodes scapularis - Villar, Margarita; Ayllón, Nieves; Kocan, Katherine M; Bonzón-Kulichenko, Elena; Alberdi, Pilar; Blouin, Edmour F; Weisheit, Sabine; Mateos-Hernández, Lourdes; Cabezas-Cruz, Alejandro; Bell-Sakyi, Lesley; Vancová, Marie; Bílý, Tomáš; et al. (PloS one, 2015)
Anaplasma phagocytophilum is an emerging zoonotic pathogen transmitted by Ixodes scapularis that causes human granulocytic anaplasmosis. Here, a high throughput quantitative proteomics approach was used to characterize A. phagocytophilum proteome during rickettsial multiplication and identify proteins involved in infection of the tick vector, I. scapularis. The first step in this research was focused on tick cells infected with A. phagocytophilum and sampled at two time points containing 10-15% and 65-71% infected cells, respectively to identify key bacterial proteins over-represented in high percentage infected cells. The second step was focused on adult female tick guts and salivary glands infected with A. phagocytophilum to compare in vitro results with those occurring during bacterial infection in vivo. The results showed differences in the proteome of A. phagocytophilum in infected ticks with higher impact on protein synthesis and processing than on bacterial replication in tick salivary glands. These results correlated well with the developmental cycle of A. phagocytophilum, in which cells convert from an intracellular reticulated, replicative form to the nondividing infectious dense-core form. The analysis of A. phagocytophilum differentially represented proteins identified stress response (GroEL, HSP70) and surface (MSP4) proteins that were over-represented in high percentage infected tick cells and salivary glands when compared to low percentage infected cells and guts, respectively. The results demonstrated that MSP4, GroEL and HSP70 interact and bind to tick cells, thus playing a role in rickettsia-tick interactions. The most important finding of these studies is the increase in the level of certain bacterial stress response and surface proteins in A. phagocytophilum-infected tick cells and salivary glands with functional implication in tick-pathogen interactions. These results gave a new dimension to the role of these stress response and surface proteins during A. phagocytophilum infection in ticks. Characterization of Anaplasma proteome contributes information on host-pathogen interactions and provides targets for development of novel control strategies for pathogen infection and transmission.
Keywords: gastrointestinální trakt; membránové proteiny; signální transdukce; chaperon hsp60; Gene Expression Profiling; Membrane Proteins; Ixodes; Gene Expression Regulation; Stress, Physiological; HSP70 Heat-Shock Proteins; Gastrointestinal Tract; Signal Transduction; anotace sekvence; Salivary Glands; fyziologický stres; Chaperonin 60; Host-Pathogen Interactions; regulace genové exprese; Bacterial Proteins; Molecular Sequence Annotation; ženské pohlaví; Proteome; zvířata; Anaplasma phagocytophilum; interakce hostitele a patogenu; slinné žlázy; stanovení celkové genové exprese; klíště; proteom; Female; proteiny tepelného šoku HSP70; bakteriální proteiny; Animals